Study of Different Dimensions of Lifestyle and Some of the Factors Associated with it in Employees of Mazandaran University of Medical Sciences in 2017 - Shokooh Karimi; Farzaneh Afkhaminia; Fereshteh Talebpour Amiri (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Lifestyle is one of the most important indicators of improvement in the quality of life. Given the important role of staff as a valuable human resource, we aimed to determine different dimensions of lifestyle in employees of Mazandaran University of Medical Sciences,  azandaran, Iran, in 2017. Methods: A descriptive cross-sectional study of 186 employees was carried out. The participants were chosen through the stratified random sampling method. The Life Style Questionnaire (LSQ) was used to evaluate lifestyle. To analyze the data, we used descriptive statistics, t-test, Chi-square test, Spearman correlation coefficient, and linear regression test in SPSS. Results: The mean score of staff lifestyle was 206±22.21 (out of a total of 272 points). The lifestyle status in 59.4% of the cases was good. The lowest score was related to exercise and health. Women had higher scores in the prevention of accidents and men obtained higher scores in the domain of exercise and health. There was a significant relationship between gender and exercise and health (P=0.026), marital status and avoidance of medications and illicit drugs (P=0.036), age and prevention of accidents (P=0.005), body mass index and overall lifestyle status of the staff (P=0.004), weight control and nutrition (P=0.001), as well as disease prevention and spiritual health (P=0.001). Conclusion: Although the majority of employees had a moderate and good lifestyle, the domains of exercise and health, weight, and nutrition were not in a desirable status. We recommend adopting proper interventions for improving staff health in these domains.